Protocol of scheduling of elective surgeries of a maternity school: a methodological study. - da Silva, Jaqueline Souza; Esteves, Ana Paula Vieira dos Santos; Junior, Joffre Amim; de Rezende Filho, Jorge Fonte (Online Brazilian Journal of Nursing, 2018)
Aim: to construct a scheduling protocol and the assistance flow of elective surgeries to the Obstetric Center of a maternity ward. Method: this is a methodological, descriptive, qualitative research, of the case study type, operationalized in 2015 in a maternity hospital in the city of Rio de Janeiro. The Situational Strategic Planning proposed by Carlos Matus was used, starting from the explanatory, normative, strategic and tactical-operational moments. Results: in the explanatory moment the diagnosis of the reality of scheduling of the surgical sector was performed; in the normative moment the strategies of solution to the confrontation of the problem were proposed; in the strategic moment the viability of the strategies of solution was constructed from action plans; in the tactical-operational moment the following actions were operationalized: construction of the protocol and a flow chart of surgical scheduling. Conclusion: it is believed that these instruments, which still need to be tested and validated in the study scenario, will help manage the healthcare processes of the sector.